Fiscal adjustments: Lessons from and for the Baltic states - Violeta Klyvienė; Audronė Jakaitienė (Baltic Journal of Economics, 2022)
This paper aims to investigate the effects of various fiscal policy measures for small and open economies by analysing the implications of fiscal shocks in the Baltic countries based on data for the period from 1995 to 2018. For this purpose, we have chosen structural VAR estimation methods following Blanchard, O., & Perotti, R. (2002). An Empirical Characterization of the Dynamic Effects of Changes in Government Spending and Taxes on Output. The Quarterly Journal of Economics, 117(4), 1329-1368, approach and relied on local projections for robustness checks. We find that the impact on growth of direct taxes, government consumption and public investment is strong and persistent in the analysed cases. Although the responses of FDI to fiscal shocks are less consistent as compared to output, in most cases, we get strong and persistent negative reactions in FDI to increasing tax burden.
Keywords: E62; H2; H30; H50; 330; economic recession; fiscal multipliers; fiscal policy; Fiscal shocks; investment; the Baltic states